Pilihan Karier Sebagai Determinan Kinerja Guru Perempuan - Eustalia Wigunawati; Shakira Aulia Paramudea; Renatha Ernawati (Pusat Studi Gender, Universitas Kristen Indonesia, 2025)
Teacher performance is an important indicator of the success of educational institutions in producing competent and competitive students. Although the teaching profession is dominated by women, empirical studies examining the relationship between career choice and the performance of female teachers remain limited. This study aims to analyze the levels of career choice and performance of female teachers and to examine the relationship between career choice and the performance of female teachers in Bekasi City. This research employed a quantitative approach with a correlational method. The research subjects consisted of 88 female teachers from four schools in Bekasi City. Data were collected using the Teacher Performance Scale and the Career Choice Scale, both of which had been tested for validity and reliability. Data analysis was conducted using descriptive statistics and the nonparametric Spearman’s rho correlation test because the data were not normally distributed. The results of the descriptive analysis indicate that the performance of female teachers ranged from moderate to high, with 34.09% in the high category, 39.77% in the moderate category, and 26.14% in the low category. Meanwhile, career choice among female teachers was predominantly in the moderate category (53.41%), followed by the high category (21.59%) and the low category (25%). The results of the Spearman’s rho correlation test show a positive and significant relationship between career choice and the performance of female teachers (r = 0.404; p < 0.05), with a contribution of 16.3% (R² = 0.163). This study concludes that career choice is one of the determinants of female teachers’ performance, although its contribution is moderate. Therefore, efforts to improve the performance of female teachers should be supported through strengthened career planning and school policies that consider both internal and external factors affecting female teachers.